Molecular Markers for Prostate Cancer in Formalin-Fixed Paraffin-Embedded Tissues. (25th November 2013) - Sequeiros, Tamara; García, Marta; Montes, Melania; Oliván, Mireia; Rigau, Marina; Colás, Eva; de Torres, Inés; Morote, Juan; Reventós, Jaume; Doll, Andreas
Abstract : Prostate cancer (PCa) is the most frequently diagnosed type of cancer in developed countries. The decisive method of diagnosis is based on the results of biopsies, morphologically evaluated to determine the presence or absence of cancer. Although this approach leads to a confident diagnosis in most cases, it can be improved by using the molecular markers present in the tissue. Both miRNAs and proteins are considered excellent candidates for biomarkers in formalin-fixed paraffin-embedded (FFPE) tissues, due to their stability over long periods of time. In the last few years, a concerted effort has been made to develop the necessary tools for their reliable measurement in these types of samples. Furthermore, the use of these kinds of markers may also help in establishing tumor grade and aggressiveness, as well as predicting the possible outcomes in each particular case for the different treatments available. This would aid clinicians in the decision-making process. In this review, we attempt to summarize and discuss the potential use of microRNA and protein profiles in FFPE tissue samples as markers to better predict PCa diagnosis, progression, and response to therapy.